Urejanje podeželskega prostora - naloga integralnega ali sektorskega načrtovanja? - Prosen, Anton (Urbani izziv, 2003)
The article deals with issues in planning of the countryside, both from the aspect of former and present normative acts and practice in other countries. European Union directives for the countryside and agriculture, which should berespected in physical planning, are emphasised. In conclusion guidelines forthe formulation of planning and implementation methodology for the countryside are presented, with respect to integral and departmental planning.
Keywords: podeželje; prostorski razvoj; prostorsko planiranje; regionalno planiranje; rural area; Slovenia; Slovenija; spatial planning; strategija; urejanje prostora